An evolutionary history of the gangs and factions of Rio de Janeiro: adapting to survive - Varsori, Andrea (Palgrave's frontiers in criminology theory, 2025)
The book provides a compelling and comprehensive explanation of the puzzling resilience of the gangs that have operated in Rio de Janeiro since the 1980s. It offers a broad overview of the history of gangs and gang alliances (factions) in the whole of the city, focussing on the evolution and consistency of these groups over time, positing the link between these and the groups’ chances of survival. It draws on more than 285 articles from 15 newspapers and media outlets across a time span covering more than 40 years, supplemented with interviews with high-ranking public security officers and secondary data. Applying a novel and composite translation of biological evolutionary concepts to a complex criminological context, it focusses on three main fields of interest: territory, relations, and internal dynamics. Andrea Varsori is Senior Lecturer at the University of Huddersfield, UK. His research focuses on urban violence, and particularly on the resilience and adaptability of urban armed groups, as well as on their strategic use of violence and its trends. Since 2019, he is Co-Coordinator of the Urban Violence Research Network. His work has been published in Small Wars and Insurgencies, Terrorism and Political Violence, and Small Wars Journal. He holds a PhD in War Studies from King’s College London.